Adsorchromism: Molecular Nanoarchitectonics at 2D Nanosheets—Old Chemistry for Advanced Chromism. Issue 14 (16th May 2021) - Eguchi, Miharu; Nugraha, Asep Sugih; Rowan, Alan E.; Shapter, Joe; Yamauchi, Yusuke
Abstract: Chromism induced by changes in the electronic states of dye molecules due to surface adsorption is termed "adsorchromism" in this article. These changes of molecular electronic states are induced by protonation, aggregation, intramolecular structural changes, and other processes, depending on the surface environment. Intramolecular structural changes, such as co‐planarization and decreased molecular motion are the most characteristic and interesting behavior of dye molecules at the surfaces, resulting in spectral shift and/or emission enhancement. In this review, adsorchromism at the surfaces of layered materials are summarized since their flexibility of interlayer distance, surface flatness, and transparency is suitable for a detailed observation. By understanding the relationship between adsorchromism and the electronic states of molecules on the surfaces, it will be possible to induce some desired functions which can be realized simply by adsorption, instead of complicated organic syntheses. Thus, adsorchromism has potential applications such as effective solar energy harvesting systems, or biological/chemical sensors to visualize environmental changes. Abstract : Chromism induced by changes in the electronic state of dye molecules due to surface adsorption is termed "adsorchromism" in this article. These changes of molecules' electronic state are depending on the surface environment. Structural changes and decreased molecular mobility are the most characteristic and interesting behavior of dye molecules at the surfaces, resulting in spectral shift and/or emission enhancement.